CORRELATION BETWEEN HYDROPONIC CILANTRO VEGETATIVE GROWTH AND ACCUMULATED GROWING DEGREE DAYS (REMUNOM, 2026)
The present study aimed to evaluate the vegetative growth of cilantro (Coriandrum sativum L.) cultivated in an NFT (Nutrient Film Technique) hydroponic system in the São Francisco Valley, correlating morphological and physicochemical variables with Accumulated Growing Degree Days (GDD). The experiment was conducted in a protected environment under a completely randomized design, with ten sampling events carried out at 48-hour intervals. The variables analyzed included stem diameter (SD), water content, dry matter content, mineral matter content, and organic matter content in the stem and leaf blade, in addition to the elemental composition (carbon, hydrogen, and oxygen contents) of the aerial parts. Climatic variables were also monitored, including air temperature and relative humidity inside and outside the facility. The results showed that GDD functioned as a highly sensitive integrative variable for plant responses, exhibiting consistent correlations with structural and physiological attributes. Stem diameter emerged as the most robust morphological indicator, showing a significant correlation with GDD (r = 0.792) and fitting well to both linear and exponential models, reinforcing its role in biomass support and distribution in NFT systems. The dynamics of mineral and organic matter contents indicated a progressive structural maturation process, characterized by increasing mineral fractions and decreasing organic fractions, evidencing advancing lignification throughout the growth cycle. The adjustment of bidimensional and tridimensional models enabled the identification of the thermal zone associated with maximum physiological performance. Logistic models provided the best fits for fresh mass (R² = 0.818) and dry mass (R² = 0.781), while the tridimensional Gaussian model—relating dry mass, stem diameter, and fresh mass—showed superior performance (R² = 0.800). Optimal points identified between 218 and 227 °C·day indicate that cilantro has a relatively narrow thermal range in which it maximizes the conversion of light and thermal energy into biomass.